KEMERDEKAAN GAYA BAHASA RADITYA DIKA DALAM STAND UP COMEDY - Lubis, Mina Syanti (Institut Pendidikan Tapanuli Selatan, 2017)
Stand up comedy is a comedian stands by himself/herself on the stage to give the jokes and speaks directly before the audience and there is no companion beside him/her. Every comic in stand up comedy has characteristics difference. It can be seen from costume, the way to express the theme, the way in speaking, figure of speech, body movements, intonation and so on. The figure of speech in rhetoric is known as style in speaking. The figure of speech can assess personal style, character, and ability of a person who uses that language. Its getting better use of figure of speech its getting better a persons assessment for him, its getting worse use of figure of speech, its getting worse a persons assessment  for him. The approach of this research is qualitative by applying descriptive method. The figure of speech that used by Raditya Dika are at least repetition, hyperbole, and sarkasme.  The skill to use the figure of speech gives jokes for the audience. Raditya Dika conveys the rant become a joke. He has high creativity to express a problem in daily living by using language that invites laughter.